The endocannabinoid system and retinoic acid signaling combine to influence bone growth. (1st June 2021) - Fraher, Daniel; Mann, Robert J.; Dubuisson, Matthew J.; Ellis, Megan K.; Yu, Tingsheng; Walder, Ken; Ward, Alister C.; Winkler, Christoph; Gibert, Yann
Abstract: Osteoporosis is an increasing burden on public health as the world-wide population ages and effective therapeutics are severely needed. Two pathways with high potential for osteoporosis treatment are the retinoic acid (RA) and endocannabinoid system (ECS) signaling pathways. We sought to elucidate the roles that these pathways play in bone development and maturation. Here, we use chemical treatments to modulate the RA and ECS pathways at distinct early, intermediate, and late times bone development in zebrafish. We further assessed osteoclast activity later in zebrafish and medaka. Finally, by combining sub-optimal doses of AR and ECS modulators, we show that enhancing RA signaling or reducing the ECS promote bone formation and decrease osteoclast abundance and activity. These data demonstrate that RA signaling and the ECS can be combined as sub-optimal doses to influence bone growth and may be key targets for potential therapeutics.